Síntese e análise estrutural de novos dihaloorganoteluratos(II) monoaniônicos. - Faoro, Eliandro (2006)
In this dissertation the synthesis and structural characterization of the new series of monoanionic dihaloorganyltellurates(II) compounds with a general formula (C5H6N)[mesTeX2] is presented. Dimesitylditelluride (mesTe)2 reacts with resublimed iodine in toluene and then with (C5H6N)+X- (X = I, Br e Cl), to give the compounds: (C5H6N)[mesTeI2] (1), (C5H6N)[mesTeIBr] (2) and (C5H6N)[mesTeICl] (3). The synthesis of (C5H6N)[mesTeBr2] (4) and (C5H6N)[mesTeBrCl] (5) occurred by the reaction of dimesitylditelluride (mesTe)2, bromine and pyridinium halides (C5H6N)+X-, X = Br (4) and Cl (5), in toluene. The compound (C5H6N)[mesTeCl2] (6) was obtained by the reaction of dimesitylditelluride, chlorine e pyridinium chloride (C5H6N)+Cl-, in toluene. The compounds 1 and 2 belong to the monoclinic space group P21/n, 3 to the orthorhombic, space group P212121. The compounds 4, 5 and 6 crystallizes in the space group P21/c, monoclinic system. The compounds show general structural characteristic and are very similar because they present a relationship tellurium-halide secondary bond and hydrogen bonds with the halides. The anionic fragments [mesTeI2]- and [mesTeIBr]- of 1 and 2 are assembled as dimers by reciprocal, secondary Te...X interactions, linked also to the pyridinium cations through μ-NH...X bonding. The compounds 3, 4, 5 and 6 do not presents secondary bonds Te...X, only (NH...X) hydrogen bonds, between the anionic fragments [mesTeX2]- and the pyridinium cations (C5H6N)+.